Gharar : Hakikat dan Pengaruhnya Terhadap Akad - Aksamawanti Aksamawanti (Syariati: Jurnal Studi Al-Qur'an dan Hukum, 2019)
All activities in the aspect of muamalah requierd clear rules, gharar is one of the terms mu’amalah that must be avoided and prohibited in Islam beside usury and maysir. Gharar is an element that contains obscurity and disguises that can occurin the subject, shighat and covenant objects. Knowing the elements of gharar canhave very important uses in relation to the validity of a contract. The Gharar ban has the goal that no parties will commit to be harmed, because they do not get the irrights, and so that there is no dipute and hostility between them.